Challenges in moving from Ad-Hoc to Planned Mine Technology Innovation (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Why Innovate in Mining? ?Obvious, right? ?Increase productivity and profitability ?Improve safety and ergonomics ?Improve our environmental record and eliminate liabilities ?Implement process control methodology ?Introduce information systems technology to gain control ?Low hanging fruit ?Reference ?Heather Ednie, Innovation CIM Magazine Feb. 2006 ?Peck & Skinner, Getting better bang for your buck with technology